Heterotopic gastric mucosa (inlet patch): endoscopic prevalence, histopathological, demographical and clinical characteristics - Poyrazoglu, O. K.; Bahcecioglu, I. H.; Dagli, A. F.; Ataseven, H.; Celebi, S.; Yalniz, M. (Wiley, 2009)
Heterotopic gastric mucosa (HGM) is found in the cervical oesophagus, just below the upper oesophageal sphincter, and has generally been overlooked by endoscopists. The objective of the present study is to determine endoscopic prevalence and histopathological and clinical characteristics of HGM and to classify patients according to their clinicopathological features. A total of 911 consecutive patients (436 M and 475 F) who were admitted to our Endoscopy Unit were examined. HGM type and the presence of Helicobacter pylori (Hp) either in the stomach or in the HGM were histopathologically evaluated. Of the 911 patients, 33 (25 M and 8 F) were found to have HGM. HGM prevalence was determined to be 3.6%. On the basis of HGM patients' symptoms, only dysphagia was significantly correlated with the size of HGM (p < 0.05). Hp was positive in 29.2% of HGM. Clinicopathological classification of the patients showed that 20 patients were HGM type 1 and 13 were HGM type 2. None of the patients had HGM type 3, 4 or 5. Prevalence of HGM was 3.6%. Dysphagia was found related with the size of HGM. This may be associated with larger HGMs' causing more acid secretion.
Keywords: Upper Esophagus; Cervical Esophagus; Helicobacter-Pylori; Primary Adenocarcinoma; Classification